The importance of scientific data and historical heritage of the geophysical and astronomical observatory of coimbra university for the study of geophysical sciences. Issue 1 (29th June 2022) - Gomes, Ana; Ramos, Anabela; Figueiredo, Fernando; Ribeiro, Paulo
Abstract: The Geophysical and Astronomical Observatory of the University of Coimbra (OGAUC) was officially created in 2013 after merging of two historical institutions: the Astronomical Observatory and the Geophysical Institute. As a result of almost 200 years of observations and research in astronomy and geophysical sciences, the OGAUC possesses a unique and valuable collection of long‐term observational and instrumental records. These data have an indispensable value in current geophysical and climatic studies, being among the most complete and significant in Portugal and the world. The OGAUC's data collections are complemented by a vast technical‐scientific production such as reports, research memoranda, articles, books, and instruments. This archive is largely not inventoried and poorly studied (particularly concerning meteorological, geomagnetic, and seismological data). This paper highlights the importance of the OGAUC's extensive data collection and discusses the difficulties and barriers related to its inventorying, preservation, and dissemination to the scientific community, policymakers, stakeholders, and the general public. Abstract : The importance of scientific data and historical heritage of the Geophysical and Astronomical Observatory of Coimbra University for the study of geophysical sciences.